Carbon-Coated Porous Aluminum Foil Anode for High-Rate, Long-Term Cycling Stability, and High Energy Density Dual-Ion Batteries - Tong, Xuefeng (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.